2012
DOI: 10.1371/journal.pone.0033252
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the G121V Dihydrofolate Reductase Mutant: Lessons from a Transition-State Inhibitor Complex

Abstract: It is well known that enzyme flexibility is critical for function. This is due to the observation that the rates of intramolecular enzyme motions are often matched to the rates of intermolecular events such as substrate binding and product release. Beyond this role in progression through the reaction cycle, it has been suggested that enzyme dynamics may also promote the chemical step itself. Dihydrofolate reductase (DHFR) is a model enzyme for which dynamics have been proposed to aid in both substrate flux and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 47 publications
(103 reference statements)
2
40
0
Order By: Relevance
“…Indeed, the G123V mutation in MpDHFR has little effect on the single turnover rate constant or its observed KIE at pH 7, consistent with the proposal that interactions between the FG and M20 loops do not play a significant role in MpDHFR catalysis. 49 Binding of NADPH and the inhibitor methotrexate to EcDHFR-G121V forms a putative mimic of the transition state and causes the enzyme to adopt a closed conformation, 26 confirming that EcDHFR-G121V is capable of forming this conformation for hydride transfer. However, the mutation leads to aberrant millisecond conformational switching of the M20 and FG loops, 26 as would be expected when the closed conformation is strongly destabilised, suggesting that these motions are anti-catalytic and destabilise the optimum active site configuration.…”
Section: Network Of Coupled Motionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the G123V mutation in MpDHFR has little effect on the single turnover rate constant or its observed KIE at pH 7, consistent with the proposal that interactions between the FG and M20 loops do not play a significant role in MpDHFR catalysis. 49 Binding of NADPH and the inhibitor methotrexate to EcDHFR-G121V forms a putative mimic of the transition state and causes the enzyme to adopt a closed conformation, 26 confirming that EcDHFR-G121V is capable of forming this conformation for hydride transfer. However, the mutation leads to aberrant millisecond conformational switching of the M20 and FG loops, 26 as would be expected when the closed conformation is strongly destabilised, suggesting that these motions are anti-catalytic and destabilise the optimum active site configuration.…”
Section: Network Of Coupled Motionsmentioning
confidence: 94%
“…49 Binding of NADPH and the inhibitor methotrexate to EcDHFR-G121V forms a putative mimic of the transition state and causes the enzyme to adopt a closed conformation, 26 confirming that EcDHFR-G121V is capable of forming this conformation for hydride transfer. However, the mutation leads to aberrant millisecond conformational switching of the M20 and FG loops, 26 as would be expected when the closed conformation is strongly destabilised, suggesting that these motions are anti-catalytic and destabilise the optimum active site configuration. 26 The EcDHFR-M42W complex with NADPH and methotrexate also forms a closed conformation and shows slower millisecond motion than the wild-type enzyme.…”
Section: Network Of Coupled Motionsmentioning
confidence: 94%
“…18 On the other hand, the transition state of EcDHFR-G121V, modeled by the E·NADPH·MTX complex for NMR and X-ray studies, 3,21 has been shown to form a closed complex (as is necessary for catalysis to occur) but with significant excursions of the FG and M20 loops away from the accurate alignment required for reaction. 21 This is in agreement with previous computational studies, which showed that the G121V mutation leads to an altered transition state structure in EcDHFR, with a concomitant increase in the activation free energy barrier. 17,20 These results suggest that EcDHFR-G121V is capable of adopting the closed conformation but that the conformational fluctuations are different from those of the wild-type enzyme.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…When the closed conformation is destabilized by mutations in the FG loop, the occluded conformation becomes the ground state of EcDHFR in the Michaelis complex. Reaction can then only occur from a minor population of the overall ensemble, 21 as NADPH and DHF are held in positions unsuitable for reaction in the occluded conformation. 3 As MpDHFR lacks the key residue that stabilizes the occluded conformation (DOI: 10.1021/bi500507v), loss of hydrogen bonds that stabilize the closed conformation in MpDHFR will simply lead to formation of a destabilized closed conformation rather than favoring an occluded conformation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A similar example is found in the E. coli DHFR enzyme, in which the FG and GH loops compete for interactions with the active-site Met20 loop [49]. Amino acid substitutions in either the FG and GH loops that disrupt these interactions lead to decreases in catalytic efficiency [50][51][52] and changes to the µs-ms timescale Met20 loop dynamics [53][54][55].…”
Section: Discussionmentioning
confidence: 59%